Reference Ranges of Ductus Arteriosus Derived by Cardio-Spatiotemporal Image Correlation from 14 to 40 Weeks of Gestation - Traisrisilp K. (2014)
Objective: To construct reference ranges of fetal ductus arteriosus (DA) derived by volume datasets of cardio-spatiotemporal image correlation (cardio-STIC). Methods: Cardio-STIC volume datasets were acquired from low-risk singleton pregnancies with a reliable gestational age from 14 to 40 weeks. In offline analysis with 4D View version 9, fetal DA was measured in the transverse ductal arch view with orthogonal control in the multiplanar view. The reference ranges of the DA and Z-score equation were constructed against gestational weeks and biparietal diameter (BPD) as independent variables. Results: A total of satisfactory 606 volumes were analyzed. The reference ranges for predicting means and SDs of fetal DA were constructed based on the best-fit regression model. Mean DA (mm) was best predicted by linear model as a function of GA (weeks) and BPD (cm) as follows: Predicted DA diameter (cm) = -0.051 + 0.014 × GA (weeks) (r = 0.84) and Predicted DA diameter (cm) = -0.015 + 0.053 × BPD (cm) (r = 0.83). Models for Z-score calculation and centile charts for predicting fetal DA were also provided. Conclusion: Reference ranges of the fetal DA and Z-score model are provided. These may serve as a useful tool in the assessment of fetal DA, especially in fetal cardiac anomalies or in monitoring fetuses exposed to maternal indomethacin. Copyright © 2013 S. Karger AG, Basel.